contestada

Explain how the Quotient of Powers Property was used to simplify this expression.

three to the fourth power all over nine equals three squared

By simplifying 9 to 32 to make both powers base three and adding the exponents
By simplifying 9 to 32 to make both powers base three and subtracting the exponents
By finding the quotient of the bases to be one third and simplifying the expression
By finding the quotient of the bases to be one third and cancelling common factors

Respuesta :

Answer:

The answer is option 2, by simplifying 9 to 3² to make both powers base 3 and subtracting the exponents.

Step-by-step explanation:

You have to make the expressions into the same base :

[tex] \frac{ {3}^{4} }{9} = \frac{ {3}^{4} }{ {3}^{2} } [/tex]

Next, you have to apply Indices Law :

[tex] {a}^{m} \div {a}^{n} \: ⇒ \: {a}^{m - n} [/tex]

[tex] {3}^{4} \div {3}^{2} [/tex]

[tex] = {3}^{4 - 2} [/tex]

[tex] = {3}^{2} [/tex]

By simplifying 9 to 3² to make both the powers base 3 as well as subtracting the exponents. A further explanation of the given question is below.

According to the question,

The equation will be:

→ [tex]\frac{(3)^4}{9} = \frac{(3)^4}{(3)^2}[/tex]

By applying the Indices law i.e.,

→ [tex]\frac{a^m}{a^n} = a^{m-n}[/tex]

then, we get

→ [tex]\frac{3^4}{3^2}[/tex]

→ [tex]3^{4-2}[/tex]

By subtracting the powers, we get

→ [tex]3^2[/tex]

Thus the above answer i.e., option B) is the correct approach.

Learn more:

https://brainly.com/question/19660607